Relationship Between Parents' Knowledge and Behavior with The Incidence of Caries In Children Aged 3-5 Years - Dessylindra, Herningrum; Purnamawati, Dewi (Program Pascasarjana UIN Sumatera Utara, 2025)
Parental knowledges plays a crucial role in shaping behaviors that support children's oral hygiene. This is studing aims to analyze the relationship between parental knowledge and behaviors with the occurrence of dental caries in children aged 3-5 years. An analytical cross-sectional study was conducted at Posyandu Kenanga 3 in Kelurahan Bugel, Tangerang City, involving 25 parents and their children. Data were collected through questionnaires and observations over three months from February 1 to May 24, 2025. The are results indicate that parental age, education, and access to health information significantly influence children's dental health. Parental involvement in children's dental care is affected not only by age but also by their understanding of oral health practices. The willingness of parents, especially mothers, to take their children for dental care is influenced by the child’s developmental stage. Parental knowledge is key to effective dental health care; thus, enhancing parental knowledge and behaviors is strongly recommended to prevent future issues and establish healthy habits in children from an early age.